CORAK PENDIDIKAN ISLAM INKLUSIF - Moh. Mizan Habibi (EL-TARBAWI, 2017)
Islam as the majority religion in Indonesia has an important role in maintaining inter-religious harmony. As is known in the Qur'an it is written that Islam is a religion of rahmatan lil 'alamin so that religion should provide peace and tranquility anywhere, including in Indonesia. This has implications for the process of implementing Islamic education in Indonesia. However, the reality on the ground is that there are still frequent claims and justifications for the truths produced by each party, religious learning is still doctrinal, and Islamic education material is formulated and delivered using only one perspective. To respond to the phenomenon that becomes academic anxiety, it is necessary to formulate a more humanistic Islamic education. So, Islamic education that is built must be adjusted to the reality that exists in the community. If the Indonesian nation juridically accommodates religion and internally Muslims are divided, the design of Islamic education must be developed in an inclusive, accommodative-selective and multi-perspective manner.Keywords: inclusive Islamic education, accommodative, multi-perspectives